2013
DOI: 10.1016/j.jamcollsurg.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measures of Visceral Adiposity and Body Mass Index in Predicting Rectal Cancer Outcomes after Neoadjuvant Chemoradiation

Abstract: BACKGROUND The association between body mass index as a measure of obesity and rectal cancer outcomes has been inconsistent. Radiologic measures of visceral adiposity using CT scans have not been well characterized among rectal cancer patients. The objective of this study was to examine quantitative radiologic measures of visceral obesity compared with body mass index in predicting patient outcomes among patients undergoing neoadjuvant chemoradiation and resection for locally advanced rectal cancers. STUDY D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 39 publications
(62 reference statements)
6
126
1
Order By: Relevance
“…The main characteristics of the 29 included studies are summarized in Table 1. Of the included studies, 14 were conducted in North America [11,12,21,22,24,25,28,32,34,37,38,41,42,44], five were conducted in Europe [14,26,27,30,40], six were conducted in Asia [15,23,31,33,35,36], three were conducted in Oceania [13,29,43], and one study included multiple cohorts from North America and Europe [39].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The main characteristics of the 29 included studies are summarized in Table 1. Of the included studies, 14 were conducted in North America [11,12,21,22,24,25,28,32,34,37,38,41,42,44], five were conducted in Europe [14,26,27,30,40], six were conducted in Asia [15,23,31,33,35,36], three were conducted in Oceania [13,29,43], and one study included multiple cohorts from North America and Europe [39].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…38,40 One study used three- dimensional reconstruction to calculate VFV. 25 Nine image analysis softwares were reported.…”
Section: Ctbc Analysismentioning
confidence: 99%
“…25 Two studies found no relationships with wound infection rates and visceral obesity. 33,38 Overall postoperative complications Lieffers et al found sarcopenia was associated with an increased rate of postoperative infection identified from ICD-10 diagnostic codes (23.1% vs 12.6%, p ¼ 0.036). 28 In multivariate analysis, sarcopenia independently predicted postoperative infections (OR 4.6; 95%, CI ¼ 1.5e13.9).…”
Section: Operative Timementioning
confidence: 99%
See 1 more Smart Citation
“…The measure of visceral to subcutaneous fat areas was thought to be a more accurate indicator of abdominal or visceral adiposity and quantitative measures of visceral adiposity were correlated with clininopathological variables as well as survival outcomes in a retrospective study of patients treated with chemoradiation [103]. Patients who had higher visceral fat had less T-stage downstaging while patients with no or partial response and high adiposity comprised the worst group in terms of disease-free survival.…”
Section: Constitutional Patient Factorsmentioning
confidence: 99%